Complications and side effects of cervical and lumbosacral selective nerve root injections - Huston, Christopher W.; Slipman, Curtis W.; Garvin, Cyndi (Archives of physical medicine and rehabilitation, 2005)
Huston CW, Slipman CW, Garvin C. Complications and side effects of cervical and lumbosacral selective nerve root injections. To determine the incidence of complications and side effects of cervical and lumbosacral selective nerve root injections (SNRIs). Prospective, nonrandomized controlled trial of consecutive patients with independent interviews for immediate, 1-week, and 3-month follow-ups. Tertiary, academic spine center. Of 160 patients eligible for SNRI, 151 underwent 306 SNRIs (study group). Sixty patients who had not undergone any intervention served as the control group. Diagnostic and therapeutic fluoroscopically guided cervical and lumbosacral SNRIs. Lidocaine (Xylocaine) was used in the diagnostic injections and a mixture of lidocaine and betamethasone was used in the therapeutic injections. Complications and side effects experienced during the procedure were recorded by the interventionalist. Side effects and complications experienced immediately, 1 week, and 3 months after injection were determined through independent interviews using a questionnaire format. The control group was independently interviewed using the same questionnaire. There were no major complications, such as death, paralysis, spinal nerve injury, infection, or allergic reaction, during the study. Ninety-one percent of subjects had no side effects during the procedure. A positive response on interview was reported by 39.4% of the study subjects immediately after the procedure. Lumbosacral SNRI side effects were as follows: increased pain at the injection site (17.1%); increased radicular pain (8.8%); lightheadedness (6.5%); increased spine pain (5.1%); nausea (3.7%); nonspecific headache (1.4%); and vomiting (0.5%). Immediate side effects from cervical SNRI were as follows: increased pain at injection site (22.7%); increased radicular pain (18.2%); lightheadedness (13.6%); increased spine pain (9.1%); nonspecific headache (4.5%); and nausea (3.4%). At the 1-week interview, comparison of the study and control groups showed statistical significance for the following: pain at injection site, cervical ( P=.001) and lumbar ( P=.005); nonspecific headache, cervical ( P=.019); and nonspinal headache, cervical ( P=.002). At 3 months, 2 subjects complained of increased neck pain and 1 reported heartburn and fluid retention. Two lumbar SNRI subjects were lost to follow-up. There were no major complications with cervical and lumbosacral SNRIs, although various minor side effects occurred.